Tinjauan Geografi dalam Pengembangan Desa Wisata Serang di Kecamatan Karangreja Kabupaten Purbalingga - Azhari, Burhan; Santoso, Apik Budi (Geo-Image, 2019)
The tourism sector is widely used as a source of regional income, such as those in Purbalingga Regency with the development of Serang Tourism Village, but tourism development has not fully benefited the community, so this needs to be studied more deeply in tourism where there are important elements of tourism supply and demand, this is where tourism geography plays a role in providing spatial information from existing tourism supply and demand conditions and is able to provide a description, in this study, it also has a goal of how to find better strategies for better tourism development, using SWOT analysis. The results of this study indicate that the tourism conditions in Serang Tourism Village have strengths and weaknesses in the existing inventory element, while for demand, this shows that tourists consider the elements of existing tourism offers, there are good elements and there are elements that are still weak, while for the SWOT analysis the values ​​of X: 0.99 and Y: 0.62 obtained, the tourism situation shows Cuadraan I, the strategy that needs to be done is Growth Oriented Strategy, which means that tourism conditions are in good condition, but must strengthen all aspects of tourism offerings and fix existing weaknesses to create development that provides shared prosperity.